Characteristics and preliminary healing ability of polydimethylsiloxane elastomers - Thi Sinh Vo; Truong Sinh Nguyen; Byounghyun Jeon; Tran Thi Bich Chau Vo; Soobean Han; Seung-Hyun Lee; Kyunghoon Kim (Journal of Materials Research and Technology)
Flexible polydimethylsiloxane (PDMS)-based elastomers are extensively used in microfluidics and microelectronics due to their exceptional thermal stability, chemical inertness, flexibility, and stretchability. These properties make PDMS ideal for use as bendable and stretchable substrates, lab-on-a-chip components, and various other device elements. However, despite their widespread application, the detailed characteristics of cured PDMS elastomers, particularly those produced with varying weight ratios of the base (Part A) and curing agent (Part B), have not been fully explored. This includes their chemical, mechanical, and adhesive properties, as well as their decomposition chemistry and thermal resistance under different conditions, such as in air and nitrogen atmospheres. In this study, flexible PDMS elastomers were fabricated by mixing different weight ratios of Part A and Part B to form various curing networks via a hydrosilylation reaction. The resulting elastomers were analyzed to understand their chemical and thermal properties, as well as the underlying mechanisms driving these characteristics. The Si–H bonds in Part B facilitated the formation of curing networks among the vinyl-group-containing siloxane backbones. During thermal degradation, dimethylsilanone was generated over a wide temperature range, with associated pyrolysis products observed during its release. Additionally, mechanical properties such as tensile stress, elongation at break, and peel adhesion were evaluated to clarify the effects of curing reactions and molecular interactions on the performance of the elastomers. Notably, these cured PDMS elastomers demonstrated preliminary self-healing abilities when Part B was applied to damaged regions. This study sheds light on the primary characteristics and healing potential of commercial PDMS elastomers, highlighting their suitability for applications like heat-resistant adhesives, thermal protective coatings, and self-healing materials.